Modification of Poly(lactic acid) by the Plasticization for Application in the Packaging Industry - Gzyra-Jagieła, Karolina; Sulak, Konrad; Draczyński, Zbigniew; Podzimek, Stepan; Gałecki, Stanisław; Jagodzińska, Sylwia; Borkowski, Dominik (Polymers, 2021)
Plastic products, especially in the packaging industry, have become the main commodities penetrating virtually every aspect of our lives. Unfortunately, their omnipresence is not neutral to the natural environment. Pollution in the form of microplastics is a global problem. Therefore, green technologies that enter into the circular economy become an important topic. As part of the research work, the modification of poly(lactic acid) has been studied for use in the packaging industry. Due to its intrinsic rigidity, plasticizing substances had to be introduced in PLA in order to improve its plastic deformability. Both high-molecular compounds such as ethoxylated lauryl alcohol, block copolymer of ethylene oxide and propylene oxide, and ethoxylated stearic acid as well as low-molecular compounds such as di-2-ethylhexyl adipate, di-2-ethylhexyl sebacate, and triethyl citrate were used. The samples extruded from plasticized polymers were characterized using differential scanning calorimetry, thermal gravimetric analysis, and mechanical properties including Young's modulus. The melt flow rate (MFR) and molar mass distribution were determined. For all modified samples the glass transition temperature, depending on the plasticizer used, was shifted towards lower values compared to the base polymer. The best result was obtained for di-2-ethylhexyl adipate (ADO) and di-2-ethylhexyl sebacate (SDO). The elongation at break increased significantly for ADO at about 21%. The highest elongation was obtained for SDO (about 35%), although it obtained a higher glass temperature. The degradation of the polymer was not observed for both plasticizers. For these plasticizers (ADO and SDO) it also lowered Young's module by about 26%, and at the infrared spectrum deformation of peaks were observed, which may indicate the interaction of the ester carbonyl group of PLA with plasticizers. Therefore it can be concluded that they are good modifiers. The selected plasticizers that are used in the production of food contact materials, in particular in the production of PVC (polyvinyl chloride) food films, also exhibited great potential to be applied to PLA food films, and exhibit better properties than the citrate, which are indicated in many publications as PLA plasticizers.
Keywords: polylactic acid; FTIR-ATR; biodegradable polymers; SEC-MALS; plasticization